Analisis Pengendalian Kualitas Produksi Bushing Suspensi Menggunakan Metode Failure Mode and Effect Analysis (FMEA) - Ibrahim Brilian; Gunawan Mohammad (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
This study analyzes the quality control of polyurethane suspension bushing production at Han Jaya Fabrication, a home industry located in Jepara, Central Java. The main issues identified include semi-manual production processes, high operator-skill dependency, and the absence of formally documented quality control procedures. The research employs Failure Mode and Effect Analysis (FMEA), a systematic Total Quality Management approach to identify potential failure modes, analyze their effects, and prioritize corrective actions based on Risk Priority Number (RPN) values. The analysis identified 12 failure modes across five core production processes, with the highest RPN values found in bushing diameter out of tolerance (RPN=315), defective product passing inspection (RPN=315), inconsistent bushing surface quality (RPN=294), and cutting dimension non-conformance (RPN=252). Recommended corrective actions focus on process standardization through written SOPs, implementation of jigs/fixtures, preventive maintenance schedules, and multi-layer inspection systems. These findings are intended to serve as a foundation for Han Jaya Fabrication in implementing Total Quality Management (TQM) principles to improve product consistency and competitiveness.